An architecture for modular grading and feedback generation for complex exercises - Striewe, Michael (Science of computer programming, 2016)
Grading and feedback generation for complex open exercises is a major challenge in e-learning and e-assessment. One particular instance of e-assessment systems designed especially for grading programming exercises is JACK. This paper aims to discuss and evaluate key architectural concepts of JACK in terms of components, interfaces, and communication. It is shown how the architectural concept stands the test in an actual large scale deployment. •Modular architecture for e-assessment-systems.•Discussion of static and dynamic properties of architecture.•Reports from eight years of development and practical use.